SERIAL KASUS EKSTUBASI FAST-TRACK PADA BEDAH JANTUNG TERBUKA - Hapsari, Paramita Putri; Pratomo, Bhirowo Yudo; Putro, Bambang Novianto (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2024)
Fast-track extubation (FTE) has been shown to reduce the incidence of prolonged mechanical ventilation, resulting in shorter hospitalization, lower morbidity, mortality, and hospital costs. We present a case series of fast-track extubation involving two females aged 31 and 33 with Atrial Septal Defect (ASD) and a 33-year-old male with Ventricular Septal Defect (VSD) scheduled for defect closure. These patients were in good clinical condition with normal biventricular function and a low probability of pulmonary hypertension. The anesthesia and surgery procedures proceeded smoothly, with cardiopulmonary bypass time < 90 minutes, aortic cross-clamp time < 60 minutes, no residual shunt, acceptable lactate and blood gas analysis, stable hemodynamic with low doses of vasoactive agents, and adequate analgesia. Following the successful execution of the fast-track extubation protocol in the operating theatre, the patients were transferred to the intensive care unit (ICU) where they received postoperative management. The total ICU length of stay was < 24 hours, demonstrating the safety and efficacy of FTE for simple cardiac procedures and favourable outcomes. This approach is aimed at accelerating patient recovery, reducing complications, and enhancing overall surgical outcomes.